2017
DOI: 10.1289/ehp277
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyl and Organochlorine Pesticide Concentrations in Maternal Mid-Pregnancy Serum Samples: Association with Autism Spectrum Disorder and Intellectual Disability

Abstract: Background:Polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs) are neurodevelopmental toxicants, but few studies have examined associations with autism spectrum disorder (ASD).Objectives:We aimed to determine whether prenatal exposure to PCBs and OCPs influences offspring risk of ASD and intellectual disability without autism (ID).Methods:We conducted a population-based case–control study among Southern California births, including children with ASD (n = 545) meeting Diagnostic and Statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
165
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 171 publications
(202 citation statements)
references
References 39 publications
9
165
1
6
Order By: Relevance
“…Some of these studies reported positive associations between residential proximity to pesticides during the first trimester (Roberts et al, 2007) or any point during pregnancy, especially the third trimester (Shelton et al, 2014). In contrast, studies using maternal biological markers to assess exposures have reported no association between pesticides and ASD (Lyall et al, 2017b) or autistic behaviors (Millenson et al, 2017). Another study using self-reported pesticide exposure data attempted to correct for exposure misclassification and found that the association varied when corrected for different degrees of exposure misclassification, leading the authors to suggest future validation studies to be conducted (Keil, Daniels, & Hertz-Picciotto, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Some of these studies reported positive associations between residential proximity to pesticides during the first trimester (Roberts et al, 2007) or any point during pregnancy, especially the third trimester (Shelton et al, 2014). In contrast, studies using maternal biological markers to assess exposures have reported no association between pesticides and ASD (Lyall et al, 2017b) or autistic behaviors (Millenson et al, 2017). Another study using self-reported pesticide exposure data attempted to correct for exposure misclassification and found that the association varied when corrected for different degrees of exposure misclassification, leading the authors to suggest future validation studies to be conducted (Keil, Daniels, & Hertz-Picciotto, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…During the revision of this paper, high serum levels of PCB-153 and PCB-138 in banked maternal second trimester serum samples were shown to be related to increased autism risk [107]. Both are enriched in ASG's (Fig 4).…”
Section: Other Metalsmentioning
confidence: 89%
“…High serum levels of PCB's in banked second trimester maternal samples associated with an increased risk of autism (particularly so for PCB138/158 and PCB153 ) [107]. Prenatal use in the first trimester associated with autism development in boys [120].…”
Section: Polychlorinated Biphenyls (Pcb)mentioning
confidence: 97%
“…Two additional variables for total PBDEs and PCBs were created by summing the individual concentrations of congeners with detection rates >60% (Sum PBDE and Sum PCB), as previously described (Lyall et al 2015, 2016). We also examined the sum of congeners with detection rates >80% but we did not find any differences compared with the less stringent criteria.…”
Section: Methodsmentioning
confidence: 99%